Scientific, educational and organizational activities of professor M. I. Stukovenkov - Ilina, O. V. (History of science and technology, 2013)
The article highlights the most significant achievements of an eminent scientist, dermatovenereologist, Director of Kiev dermatological clinic, Professor of St. Vladimir imperial university M.I. Stukovenkov (1842 – 1897).